2012
DOI: 10.1093/nar/gks143
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid and androgen receptors combine to achieve tissue specific control of human prostatic transglutaminase expression: a novel regulatory network with broader significance

Abstract: In the human prostate, expression of prostate-specific genes is known to be directly regulated by the androgen–induced stimulation of the androgen receptor (AR). However, less is known about the expression control of the prostate-restricted TGM4 (hTGP) gene. In the present study we demonstrate that the regulation of the hTGP gene depends mainly on retinoic acid (RA). We provide evidence that the retinoic acid receptor gamma (RAR-G) plays a major role in the regulation of the hTGP gene and that presence of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 59 publications
(79 reference statements)
1
28
0
Order By: Relevance
“…These aggregate data suggest that LEDGF/p75 may regulate JPO2 via transcriptional as well as posttranscriptional mechanisms in a cell context-dependent manner. In addition to direct transcriptional functions, both LEDGF/p75 and JPO2 (42,43) have been implicated in chromatin remodelling (44)(45)(46), thus JPO2:LEDGF/p75 transcriptional complexes may have more potent, global gene regulatory roles with impact on additional as yet undefined transforming pathways in medulloblastoma. Interestingly, recent studies also suggest potential E3 ubiquitin ligase functions for JPO2 (44,47), thus JPO2 may also regulate signaling via posttranslational mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…These aggregate data suggest that LEDGF/p75 may regulate JPO2 via transcriptional as well as posttranscriptional mechanisms in a cell context-dependent manner. In addition to direct transcriptional functions, both LEDGF/p75 and JPO2 (42,43) have been implicated in chromatin remodelling (44)(45)(46), thus JPO2:LEDGF/p75 transcriptional complexes may have more potent, global gene regulatory roles with impact on additional as yet undefined transforming pathways in medulloblastoma. Interestingly, recent studies also suggest potential E3 ubiquitin ligase functions for JPO2 (44,47), thus JPO2 may also regulate signaling via posttranslational mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Massie et al (37) found KDM4B to be upregulated in response to androgens after 5 h, but found no change before this. On analysis of their data by Rivera-Gonzalez et al (38), six androgen response elements were identified close to the KDM4B gene. Guseva et al (39) also identified KDM4B as an AR-regulated gene by ChIP-Seq in LNCaP cells.…”
Section: Discussionmentioning
confidence: 99%
“…PSA secretion is regulated by activation of the AR, which interacts with both RARs and RXRs, forming dimers and modulating gene transcription (Rivera-Gonzalez et al, 2012), and the presence of 9cRA can alter the expression of AR target genes (Chuang et al, 2005a). Increased PSA secretion is also consistent with the observed reduction in proliferation, suggesting that cells entered a state of growth arrest, accompanied by an increased production of PSA, as expression of cellular differentiation increased.…”
Section: Discussionmentioning
confidence: 70%